Behavioral Specialization During the Neolithic—An Evolutionary Model - Vásárhelyi, Zsóka; Scheuring, István (Frontiers in Sociology, 2018)
The emergence of agriculture and complex societies during the Near-Eastern Neolithic opened a new era in human evolution. Food production seriously affected the ecological environment, and societies answered this with large-scale division of labour and specialisation. In this paper we study this transition with an individual based model framework. Our model captures the connections between the appearance of agriculture, social division of labour, and behavioural diversity. Our two main settings represent different habitats: In the pre-Neolithic habitat resources fluctuate in time and there is no large-scale food storage. In the Neolithic habitat active food production results in economic surplus. We consider a sexually reproducing social group, where individuals solve different tasks for survival. We assume that the task solving effectiveness has a genetic basis, but also improves with experience and learning. Since tasks can require more or less different skills, there is a trade-off between the genetic affinities for different tasks. Individuals are born with inherited task choice strategies that they can improve by imitating more successful peers. We have shown that for the Neolithic case both phenotypic (task choice strategy) and genetic specialisation is possible, if scarcer goods are more valuable. As the number of tasks increase, specialisation evolves only in a much larger group. Although phenotypic specialisation is often present, genetic specialisation requires strong assortativity both during imitation and mate choice. Our model shows that if economic surplus becomes available, behavioural specialisation and large-scale division of labour is likely to appear.